2015
DOI: 10.1051/0004-6361/201526604
|View full text |Cite
|
Sign up to set email alerts
|

GaiaFGK benchmark stars: abundances ofαand iron-peak elements

Abstract: Context. In the current era of large spectroscopic surveys of the Milky Way, reference stars for calibrating astrophysical parameters and chemical abundances are of paramount importance. Aims. We determine elemental abundances of Mg, Si, Ca, Sc, Ti, V, Cr, Mn, Co, and Ni for our predefined set of Gaia FGK benchmark stars. Methods. By analysing high-resolution spectra with a high signal-to-noise ratio taken from several archive datasets, we combined results of eight different methods to determine abundances on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 144 publications
7
94
0
Order By: Relevance
“…In Table 3 we report the values of the atmospheric parameters and abundances of the Gaia benchmark stars. The results we obtain with our new method are in excellent agreement with the results by Jofré et al (2015Jofré et al ( , 2018 and with Gaia-ESO, in particular for ξ (rows highlighted in yellow). We obtain very similar results, which confirms our hypothesis that the standard analysis produces good results for older stars ( 600 Myr).…”
Section: Titanium and Iron Linessupporting
confidence: 87%
See 1 more Smart Citation
“…In Table 3 we report the values of the atmospheric parameters and abundances of the Gaia benchmark stars. The results we obtain with our new method are in excellent agreement with the results by Jofré et al (2015Jofré et al ( , 2018 and with Gaia-ESO, in particular for ξ (rows highlighted in yellow). We obtain very similar results, which confirms our hypothesis that the standard analysis produces good results for older stars ( 600 Myr).…”
Section: Titanium and Iron Linessupporting
confidence: 87%
“…In this figure, we also report the values for the Gaia benchmark stars we analysed. The benchmarks are quiet stars, with log R HK < −4.8 , and we obtain the same value as Jofré et al (2015) with the new approach, as reported in Table 3. We also note that the ξ value we obtain for β Hyi is slightly higher than the values obtained for the other benchmark stars, which is mainly due to the slightly advanced evolutionary stage.…”
Section: Effect Of Stellar Activitymentioning
confidence: 57%
“…Our abundance ratios were measured for the HERMES observation of Arcturus. Literature studies provided abundance ratios for the Arcturus atlas (Hinkle et al 2000); Jofré et al (2015) also included a spectrum observed with the NARVAL spectrograph.…”
Section: A4 Comparison Of Herbs and Galah Dr2 Abundancesmentioning
confidence: 99%
“…The three host stars were found within the Hypatia Catalog 1 , an amalgamate database of stellar abundances for nearby FGKM-type stars (Hinkel et al 2014). HD 9446 was observed by 7 groups (Ramírez et al 2007;Ramírez et al 2009;Baumann et al 2010;Brugamyer et al 2011;Ramírez et al 2012;Ramírez et al 2013;Brewer et al 2016), while HD 43691 and HD 179079 were both observed by 6 groups Brugamyer et al 2011;Kang et al 2011;Petigura & Marcy 2011;Brewer et al 2016 andMarcy 2011;Maldonado et al 2013;Ramírez et al 2014;Jofré et al 2015;Brewer et al 2016;Mal- donado & Villaver 2016, respectively). All datasets are renormalized to the same solar scale within Hypatia, namely Lodders et al (2009), such that they are more easily comparable.…”
Section: Stellar Propertiesmentioning
confidence: 96%